Propagação in vitro da baunilheira (Orchidaceae) - Nunes, José Arcanjo (2013)
Two experiments were used to evaluate the effects of different concentrations of sucrose on in vitro growth of seedlings of Vanilla planifolia, and to analyze the morphological variables of V. planifolia seedlings grown in different containers, with diffe